LEVERAGING AI FOR FREELANCING current and future prospects. - Boateng, Richard, 1979- (Routledge, Taylor & Francis Group, 2025)
In recent years, the profound impact of artificial intelligence (AI) on fostering new forms of entrepreneurship has become increasingly evident. Entrepreneurs worldwide are harnessing the capabilities of AI to develop innovative solutions and create businesses that address pressing challenges.Despite the growing recognition of AI's potential, there exists a crucial need to deepen understanding and awareness surrounding how individuals are leveraging AI to establish novel ventures. Many entrepreneurs are pioneering initiatives that deploy AI technologies to tackle complex problems. This challenge revolves around the imperative to explore, document, and comprehend the diverse ways in which AI is driving the emergence of new businesses, solving real-world problems, and reshaping the entrepreneurial landscape. It underscores the necessity for entrepreneurs, researchers, and the wider community to grasp the transformative role of AI in fostering innovation and enabling the creation of businesses dedicated to addressing societal issues. Addressing this challenge will contribute to a more comprehensive understanding of the synergy between AI and entrepreneurship, paving the way for informed and impactful ventures that leverage the full potential of AI technologies.In this respect, the purpose of this book is to offer an in-depth exploration of the intersection between AI and entrepreneurial ventures. The book aims to provide a contemporary and thorough analysis of how AI is playing a pivotal role in shaping new forms of entrepreneurship across various industries. It seeks to illuminate the ways in which entrepreneurs are leveraging AI technologies to drive innovation, address challenges, and create businesses that contribute to societal progress.Through the compilation of diverse perspectives, case studies, and practical insights, the book endeavors to serve as a valuable resource for professionals, entrepreneurs, investors, and professionals seeking to understand and navigate the dynamic landscape of AI-driven entrepreneurship.